Revolutionizing Autoimmune Kidney Disease Treatment with Chimeric Antigen Receptor-T Cell Therapy - Rui Gu; Jiayi Shen; Jiayu Zhang; Jianhua Mao; Qing Ye (Research)
Autoimmune kidney diseases (AIKDs) depict a range of disorders involving immune-mediated damage to the kidneys, where conventional biologic therapies involving monoclonal antibodies often prove insufficient because of persistent autoreactive B cell reservoirs in lymphoid organs and inflammatory tissues. The appearance of chimeric antigen receptor (CAR)-T cell therapies targeting B cells has shown transformative potential, with recent clinical trials showing the remarkable efficacy of anti-CD19 CAR-T cells in achieving profound B cell depletion, reducing immune complex deposition, and ameliorating renal inflammation in AIKDs. While these results highlight the potential of CAR-T cell therapy in facilitating immune reset and overcoming treatment resistance, further clinical investigations are imperative to establish its long-term safety and sustained therapeutic benefits. This review synthesizes current evidence on CAR-T cell applications in AIKDs, discusses critical considerations for clinical translation, identifies existing limitations and challenges, and proposes strategic directions for therapeutic optimization and advancement.